A perspective on the genesis, diagnostics, and management of sickle cell disease - Md Samim Hassan; Taslima Nasrin; Ajay Mahalka; Mehboob Hoque; Safdar Ali (Egyptian Journal of Medical Human Genetics)
Abstract Background Hemoglobinopathies, including sickle cell disease (SCD), have been recognized as a major health problem globally. SCD is caused by a mutation in the GAG codon that converts glutamate to valine, resulting in sickle hemoglobin (HbS) and various clinical symptoms. Main body An estimated 300,000 new-borns are diagnosed with SCD every year which makes it a very important clinical manifestation to study. The present review aims to comprehensively explore the pathophysiology, diagnostics, and management approaches for populations affected by sickle cell disease. Different genetic forms of SCDs are also mentioned in this review. Short conclusion HbS polymerization contributes to the overall pathophysiological process of SCD. Several treatment options are available, though the US Food and Drug Administration-approved low-toxicity medication hydroxyurea is commonly used to treat SCD complications. Besides, hemopoietic stem cell transplantation and gene therapy are also two potential curative approaches. For SCD management, genetic counseling and neonatal screening at different stages play a crucial role.